RANCANG BANGUN SISTEM PAKAR UNTUK MENDIAGNOSIS PENYAKIT KULIT PADA USIA ANAK-ANAK - Gomes De Jesus, Salvador Da Costa (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Childrens health is important. Children are very susceptible to germs. Health of children should be considered by parents, especially skin diseases in children. With the skin disease diagnosis expert system can provide a solution and feedback to parents about issues in the diagnosis of skin disease in their children. This expert system itself is designed using forward chaining method is a forward chaining reasoning from facts first started to test the truth of the hypothesis . With the diagnosis of a user request, the diagnosis will be processed in the system, then the results will be presented again to the user. While making an application for a website using PHP as a scripting language and MySQL as database data storage. With the expert system user can directly consult a software system without having to consult with an expert ( a pediatrician ) . Because the application of expert system can provide a solution and feedback to the user about the problem in terms of diagnosing child illnesses.Â Key words : Expert skin diseases, Forward chaining, Children